Evaluation of Long-term Clearance Rates of Interventions for Actinic Keratosis. A Systematic Review - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, Titus Josef; Schmitz, Lutz; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, M. V. (JAMA Dermatology, 2021)
Importance Multiple interventions are available for the treatment of actinic keratosis (AK). However, most randomized clinical trials and meta-analyses focus on short-term efficacy outcomes. Objective To investigate and synthesize the long-term efficacy (≥12 months) of interventions for AK from parallel-arm randomized clinical trials. Data Sources Searches in MEDLINE, Embase, and Central were conducted from inception until April 6, 2020. The reference lists of the included studies and pertinent trial registers were hand searched. The study was completed February 27, 2021. Study Selection Two reviewers screened the titles and abstracts of 2741 records. Finally, 17 published reports (original studies and follow-up reports) referring to 15 independent randomized clinical trials with an overall sample size of 4252 patients were included. Data Extraction and Synthesis Two reviewers independently extracted data on study, patient, and intervention characteristics. Network meta-analysis (NMA) of each outcome was conducted with a frequentist approach. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidance for NMA was used to assess the certainty of evidence. The revised Cochrane risk-of-bias tool for randomized clinical trials was used to evaluate the methodologic quality. Main Outcomes and Measures Participant complete clearance, participant partial clearance, and lesion-specific clearance were the outcomes, with each assessed at least 12 months after the end of treatment. Results Data from 15 independent randomized clinical trials including 4252 patients were extracted and synthesized. Ten studies were included in an NMA for the outcome of participant complete clearance, with photodynamic therapy with aminolevulinate (ALA-PDT) showing the most favorable risk ratio (RR) compared with placebo (RR, 8.06; 95% CI, 2.07-31.37; GRADE, moderate), followed by imiquimod, 5% (RR, 5.98; 95% CI, 2.26-15.84; GRADE, very low), photodynamic therapy with methyl aminolevulinate (MAL-PDT) (RR, 5.95; 95% CI, 1.21-29.41; GRADE, low), and cryosurgery (RR, 4.67; 95% CI, 1.36-16.66; GRADE, very low). Similarly, ALA-PDT had the highest RR in the NMA for lesion-specific clearance (RR, 5.08; 95% CI, 2.49-10.33; GRADE, moderate). No NMA was possible for participant partial clearance owing to poor reporting of this outcome. Conclusions and Relevance This systematic review and network meta-analysis found that therapy including ALA-PDT, imiquimod, 5%, MAL-PDT, and cryosurgery was associated with significant long-term efficacy in the NMA. This study provides data for a possible use in an evidence-based framework for selecting interventions with sustained lesion clearanc
CRIS-Team WoS Importer:2021-08-13